Comparison of the Efficacy of Two Elastic Bandages for Forearm Hematoma After Transradial Coronary Intervention - An, Lei; Du, Wei-liang; Yang, Xiao-Ning; Zhang, Chun-Yan; Xue, Zeng-Ming (Frontiers in Surgery, 2021)
Background: This study compares the efficacy of two elastic bandages in treating forearm hematoma after transradial coronary intervention. Methods: A total of 60 patients with moderate or severe forearm hematoma following transradial coronary intervention were enrolled in this study. They were randomly divided into two groups: an Idealast-haft elastic bandage group (the observation group) and a control group. The patients in the Idealast-haft elastic bandage group received compression bandaging with Idealast-haft elastic bandages and the patients in the control group received compression bandaging with Nylexorgrip elastic bandages. Observation indexes related to, for example, forearm pain, arterial pulsation, blistering, skin color, and hemostasis time, were compared between the two groups. Results: The results revealed that the times taken for pain disappearance, arterial pulse recovery, blister disappearance, skin color recovery, and compression hemostasis were significantly shorter in the Idealast-haft elastic bandage group than in the control group, and the differences were statistically significant (P < 0.05). The hematoma range and the arm circumference at the severest part of the hematoma decreased faster in the observation group than in the control group, and the differences were statistically significant (P < 0.05). Conclusion: The Idealast-haft elastic bandage is more effective than the Nylexorgrip elastic bandage in patients with forearm hematoma following transradial coronary intervention and should therefore be used in such cases.